Cezanne is a critical regulator of pathological arterial remodelling by targeting β-catenin signalling. Issue 2 (18th February 2021) - An, Weiwei; Luong, Le A; Bowden, Neil P; Yang, Mei; Wu, Wei; Zhou, Xinmiao; Liu, Chenxin; Niu, Kaiyuan; Luo, Jun; Zhang, Cheng; Sun, Xiaolei; Poston, Robin; et al.
Abstract: Aims: Pathological arterial remodelling including neointimal hyperplasia and atherosclerosis is the main underlying cause for occluding arterial diseases. Cezanne is a novel deubiquitinating enzyme, functioning as a NF-кB negative regulator, and plays a key role in renal inflammatory response and kidney injury induced by ischaemia. Here we attempted to examine its pathological role in vascular smooth muscle cell (VSMC) pathology and arterial remodelling. Methods and results: Cezanne expression levels were consistently induced by various atherogenic stimuli in VSMCs, and in remodelled arteries upon injury. Functionally, VSMCs over-expressing wild-type Cezanne, but not the mutated catalytically-inactive Cezanne (C209S), had an increased proliferative ability and mobility, while the opposite was observed in VSMCs with Cezanne knockdown. Surprisingly, we observed no significant effects of Cezanne on VSMC apoptosis, NF-κB signalling, or inflammation. RNA-sequencing and biochemical studies showed that Cezanne drives VSMC proliferation by regulating CCN family member 1 (CCN1) by targeting β-catenin for deubiquitination. Importantly, local correction of Cezanne expression in the injured arteries greatly decreased VSMC proliferation, and prevented arterial inward remodelling. Interestingly, global Cezanne gene deletion in mice led to smaller atherosclerotic plaques, but with a lower level of plaque stability. Translating, we observed a similar role for Cezanne in human VSMCs, and higher expression levels of Cezanne in human atherosclerotic lesions. Conclusion: Cezanne is a key regulator of VSMC proliferation and migration in pathological arterial remodelling. Our findings have important implications for therapeutic targeting Cezanne signalling and VSMC pathology in vascular diseases. Graphical Abstract: